PERBANDINGAN PRRESTASI BELAJAR SISWA YANG TINGGAL DI ASRAMA DAN YANG TINGGAL DI RUMAH PADA MATA PELAJARAN AGAMA KELAS XI IPA DI MADRASAH ALIYAH BAHRUL ULUM AIR EMAS - Dian Tri Lestari; Wigati Iswandhiari; Andrizal Andrizal (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
This study aims to describe the results of a comparative analysis of learning achievement in Islamic religion subjects between students who live in dormitories and students who live at home. What are the learning patterns and understanding of students who live in the dorms and live at home. How does coaching student learning take place in the hostel, is there a significant influence of student learning environment on learning achievement in religious lessons in class XI PA MA. Bahrul Ulum Air Emas. The research method used is quantitative descriptive with random sampling technique. The instruments used were observation, interview and questionnaire with Likert scale questionnaire. From the results of the study conducted a comparative analysis of the learning achievements of students living in dormitories and those living at home in religious subjects in class XI IPA Madrasa Aliyah Bahrul Ulum Air Emas on the cognitive domain (cognitive) sub-variables obtained where for students who live in boarding for 85.16% with a very high category and students living at home a of 54.17% with a high category, it can be stated that student achievement in the realm of creativity is higher for students who live in a dormitory than students who live at home with a percentage difference of 30.99 %. then in the sense domain sub-variable (affective), it was found that students living in the dormitory had a cognitive domain percentage of 83.93% with a very high category and students living at home had a cognitive domain percentage of 53.97% with a high category, it could be stated that student achievement at the realm of sense was higher students living in the dorms than students living at home with a percentage difference of 29.96%. Furthermore, the sub-variable of the intention domain (psychomotor) was obtained by students who lived in the dormitory the percentage of cognitive domain was 85.16% with a very high category and students who live at home the percentage of cognitive domain is 53.68% with a high category, it can be stated that student achievement in the realm of sense is higher for students who live in a dormitory than students who live at home with a percentage difference of 31.48%. Thus it can be stated that there is a significant difference between the learning achievements of students who live in dormitories and those who live at home in religious subjects in class XI IPA Madrasah Aliyah Bahrul Ulum Air Emas. In other words, living in a dormitory has an impact on student learning outcomes. Keywords: Comparison, Learning Achievement, Madrasa Aliyah Bahrul Ulum